Five species of the family Cyproideidae (Crustacea: Amphipoda) from Japan, with the description of a new genus and two new species - Ariyama, Hiroyuki (Zootaxa, 2016)
Five species of the family Cyproideidae (Crustacea: Amphipoda) are described from shallow sea in Japan. Cyproidea liodactyla Hirayama, 1978 was collected from Kanagawa and Shizuoka Prefectures and Ariake Sea. Morphological character of the antenna 1 in these specimens is different from the original description. Examining the paratypes of C. liodactyla, the shape of the antenna 1 in the holotype is revealed to be abnormal. Cyproidea okinawensis sp. nov. was collected from Okinawa Island. Its morphological characters resemble C. liodactyla and C. robusta Ren, 2006; however, this new species is different from the former in the smaller eyes, the narrower coxa 5 and the coloration, and from the latter in the ovoid telson. Metacyproidea gen. nov. is established with M. makie sp. nov. from Hachijo Island in Tokyo Prefecture as its type species. This new genus resembles Cyproidea, especially in the peduncular article 2 of antenna 1 with a distinct distal tooth and the posterodorsal end of urosomites with a strong projection. However, Metacyproidea can be distinguished from Cyproidea by the coalesced urosomites 2–3 and the antenna 1 with a 10–16-articulated flagellum. Moolapheonoides acutifalcatus Kobayashi & Ishimaru, 2005 and Terepeltopes dolichorhunia Hirayama, 1983 were also collected from Wakayama and Fukui Prefectures and Kanagawa, Shizuoka and Yamaguchi Prefectures, respectively. A key to species of the family Cyproideidae in Japan is provided.